Seashore - Parker, Steve; King, Dave (New York : Knopf : Distributed by Random House, 1989)
Brief text and photos introduce the animal inhabitants of the seashore, including fish, crustaceans, snails, and shorebirds.
Includes index.
Keywords: Seashore biology -- Juvenile literature; Seashore biology